OPTIMALISASI PERTUMBUHAN TANAMAN ALPUKAT (Persea americana Mill) - Rahmawati, Lina; Nurhaliza, Cut; Kamaliah, Kamaliah (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2024)
Avocado plants (Persea americana Mill) were introduced to Indonesia in the 18th century and thrive in tropical and subtropical regions. Indonesia is one of the major avocado-producing countries. Various efforts have been undertaken to optimize the quality, yield, and production of avocado plants, including the provision of essential nutrients in the growing medium. This study aims to optimize the growth of avocado plants by utilizing coffee husk waste in the planting medium. The research design employed a Randomized Block Design (RBD) with treatments of different doses of coffee husk waste: P0 (without coffee husk waste), P1 (300 g of coffee husk waste), P2 (400 g of coffee husk waste), P3 (500 g of coffee husk waste), and P4 (600 g of coffee husk waste). The parameter measured was the number of leaves 28 days after the application of coffee husk waste. The results showed that the most significant increase in the number of leaves was observed in the P4 treatment, with an average of 12.25 leaves.Key words: Avocado Plants growth, coffee husk waste